2022
DOI: 10.1108/jiabr-03-2022-0066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sovereign Sukuk as a government financing instrument with stakeholder theory: a moving forward policy from Indonesia’s experience

Abstract: Purpose This study aims to examine the performance of government projects financed by the issuance of Indonesia Sovereign Sukuk (SBSN Project) from stakeholder theory perspective and propose policy recommendations to improve its effectiveness as a government financing instrument. Design/methodology/approach The authors applied a qualitative interpretive approach in this study by conducting content analysis using stakeholder theory. Big data from official webinars about Indonesia Sovereign Sukuk issuance on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In modern society, public services such as Education, Good Health largely depend on adequate service information. The government has indeed budgeted 20 percent of the education fund from the state budget (Hidayat et al, 2023;Surachman et al, 2023). But when the world of education is now starting to enter the neoliberal era of education, according to some, such funds still feel lacking (Aflaha et al, 2021;Arhipova et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In modern society, public services such as Education, Good Health largely depend on adequate service information. The government has indeed budgeted 20 percent of the education fund from the state budget (Hidayat et al, 2023;Surachman et al, 2023). But when the world of education is now starting to enter the neoliberal era of education, according to some, such funds still feel lacking (Aflaha et al, 2021;Arhipova et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It can be defined that sukuk istishna is a certificate stating the same value issued with the aim of funding the manufacture of a product so that the product becomes the property of the certificate holder (Bappepam-LK, 2009). For example, the latest research related to sukuk in Indonesia can be seen at Armen et al, (2023), Faisal et al, (2023), and Surachman et al, (2023).…”
Section: Sukukmentioning
confidence: 99%
“…However, few recent studies (Sa'ad et al, 2022;Surachman et al, 2022;Amaliah and Aspiranti, 2017) are exception. Sa'ad et al (2022) found that sukuk have proven to be effective and reliable financial instruments for financing fiscal deficits during COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Sa'ad et al (2022) found that sukuk have proven to be effective and reliable financial instruments for financing fiscal deficits during COVID-19 pandemic. Similarly, Surachman et al (2022) documented the significant fiscal role of government sukuk in managing the state budget using stakeholder theory. Nevertheless, both studies applied qualitative research method, thus limiting the scope for using quantitative methods.…”
Section: Introductionmentioning
confidence: 99%